Institutional quality similarity, corruption distance and inward FDI in Turkey - Eren, Tevfik Mesut; Jimenez, Alfredo (Rainer Hampp Verlag, Meringerzellerstr 10, Mering, D-86415, Germany, 2015)
In this paper we investigate the impact of institutional differences as a determinant of Turkish FDI inflows from OECD economies. We focus on the corruption distance between the home and host countries as a crucial part of institutional quality. Our results confirm that FDI flows are higher when they come from countries with low differences in corruption with Turkey. Conversely, FDI flows are negatively affected when there exists a large difference in corruption between the investing country and Turkey. This is explained by the ability of firms to obtain a higher return from their resources and capabilities in those environments with a similar idiosyncrasy to the one of their home country.
Keywords: Foreign Direct Investment; Turkey; OECD countries; institutional differences; corruption; multinational enterprises